(untitled) (Encuentro, 2012)
The Molecular Biology Center at the University of Central America in Nicaragua (CBM-UCA) was founded in 1999 to strengthen biotechnology research capacity and education in Nicaragua and the Central American region. One of the first projects launched by the CBM-UCA was bio-prospecting for key industrial enzymes. This ongoing study seeks to discover and characterize restriction enzymes (RE) in bacteria, and to create a database of microorganisms isolated and identified by 16S rDNA sequencing methodology. In this paper we highlight the importance of studying the extreme environmental conditions for building knowledge of Nicaraguan biodiversity through modern molecular biology techniques such as metagenomics. The isolation of prototype enzymes such as EcoRV and ClaI is presented as an update and extension of previously undertaken work.